WOWINE DALAM KEBUDAYAAN MARITIM WAKATOBI BUTON: ANALISIS PIERRE BOURDIEU - Sumiman Udu (SASDAYA: Gadjah Mada Journal of Humanities, 2017)
Wowine (female) has a very shining and very sad footprint in the history of maritime culture Wakatobi Buton. Wowine's glorious times were when Queen Wakaa-kaa and Ratu Bulawambona came to power in Buton (Zahari, 1977/1978; Zaenu, 1984). At that time, wowine has a very strategic position in the government system of the Sultanate of Buton. Wowine's involvement in the government system of the Sultanate of Buton, not only occupied his role as queen but also became one of the conditions worthy or not someone become Sultan. The idea of wowine in the maritime culture of Wakatobi Buton was born from the research using Pierre Bordiau approach to see the habits, the realm of maritime Wakatobi Buton in the past, present, and future. This paper shows that the involvement of women in the Sultanate government system of Buton is responsible for the welfare and salvation of the empire. In the life of Buton people, women are responsible for several things, (1) taking care of the child, (2) seeking sustenance together with husband, (3) educating children, and (4) doing deeds, “amala or hope” to protect the husband's safety while in outdoors. It is further explained that the empress in the Sultanate of Buton served to: (1) become the head of Sarana Bawina, (Head of the Women's Council of the Sultanate of Buton), (2) safeguard the welfare and health of the sultan, and (3) educate the women in the sultanate. The findings were based on the method used, namely literature study and field study. Library study (script) to find information about the existence of women in the maritime culture Wakatobi Buton in the past. Field observations and interviews to determine the current condition of women in the maritime culture of Wakatobi Buton.